PENDEKATAN PENGKAJIAN AGAMA: SOSIOLOGI - Haichal Napiz; Disya Amalana Anzalna; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study examines the sociological approach to the study of religion as an effort to understand religion not only as a theological doctrine but also as a dynamic social reality. The sociological perspective emphasizes how religion influences individual and group behavior, and how social conditions shape religious practices and interpretations. This research employs a library research method with a descriptive-analytical approach using relevant academic sources. The findings show that in classical sociology, religion is viewed as a source of social cohesion (Durkheim), a driver of economic change (Weber), and a tool of power legitimation (Marx). Meanwhile, modern sociology sees religion as a transforming phenomenon through secularization, rational choice, and social construction theories. This approach also applies empirical methods, both qualitative and quantitative, to objectively analyze religious phenomena. Thus, the sociological approach provides a comprehensive understanding of religion as both a force of social integration and an agent of change in modern society.